Strategic planning of rural areas: Integrating participatory backcasting and multiple criteria decision analysis tools. (August 2022) - Sisto, Roberta; Fernández-Portillo, Luis A.; Yazdani, Morteza; Estepa-Mohedano, Lorenzo; Torkayesh, Ali Ebadi
Abstract: In rural areas, the fostering of new development paths requires a strategic planning process characterised by several kinds of uncertainties. The existence of multiple decision makers increases the complexity of the analysis, and it is difficult to identify a solution that is acceptable to the different stakeholders. This condition requires identifying appropriate methods to involve stakeholders and to reflect their different priorities. The objective of this paper is to test the suitability of an innovative methodological framework that integrates backcasting and multiple criteria decision-making tools. Backcasting would enable planners to acquire relevant knowledge of local stakeholders, while multiple criteria decision analysis (MCDA) methods would allow prioritising the alternatives. The results of the experiment offer technical advice to outline the development strategy of a Georgian Local Action Group. After a strategic analysis of the area, the Best Worst Method and the Measurement of Alternatives and Ranking according to COmpromise Solution (MARCOS) were used to prioritise the desired futures for the development of the territory and to rank the main obstacles and opportunities, while strategic actions were identified through a backcasting approach. The resulting strategy seems to reflect the vision of most of the participants and is proven to be an effective and approachable method for rural strategic planning. Nevertheless, the main strength of the approach lies in its transversality and in its applicability to face complex issues whenever different actors with different interests come into play. Highlights: The paper explores an innovative methodology integrating backcasting and MCDA tools. The proposed methodology involved rural stakeholders in strategic planning. The approach is able to face complex issues with different actors and interests.